THE ROLE OF ECONOMIC AND MATHEMATICAL MODELS AND INFORMATION TECHNOLOGIES IN MARKETING ACTIVITIES OF RETAIL ENTERPRISES - BURTSEVA, Tetiana; VASYLCHENKO, Lidiia; PEPCHUK, Serhii; PALONNA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the study of the role of economic-mathematical models and information technologies in the retail enterprises marketing activity. The essence of retail is revealed as a new direction in the development of retail trade, which covers the purchase and sale of goods to the final consumer and provides him with trade services. The importance of the economic and social functions performed by retail is emphasized. The possibility of solving retail tasks using mathematical modeling is indicated, and the important role of economic and mathematical models and methods in making management decisions in the activities of retail enterprises is also emphasized. Some basic economic-mathematical models and directions of their application in the marketing activity of retail enterprises are named. In particular, it is indicated that optimization methods and models have become widely used, which make it possible to solve the issue of optimal usage of a limited resources amount, optimal distribution of goods and services. With the help of correlation-regression analysis, the relationships between the studied characteristics are evaluated and forecasting is carried out. Network planning methods solve the issue of optimal logistic routes for the transportation of goods and work planning. Balance methods and models determine the balance of supply and demand. The possibility and necessity of applying mathematical models of inventory management, the theory of mass service, and the theory of games are also emphasized. It is indicated that an important tool for carrying out retail mathematical modeling are information technologies. Computer technologies make it possible to create economic-mathematical models, develop an algorithm for their solution, and carry out a qualitative analysis of the obtained results. The need for information technologies for the retail enterprises marketing activities was also emphasized, as a means of conducting advertising campaigns, transmitting information, maintaining relations with suppliers and customers, and conducting Internet trade.